Creative labour and collective interaction: the working lives of young jazz musicians in London. (August 2014) - Umney, Charles; Kretsos, Lefteris
This article explores the types of work undertaken by jazz musicians in London, categorizing their activities using two axes derived from debates over 'creative labour'. Firstly, the extent to which different jobs offer scope for creative autonomy and, secondly, the extent to which they involve collective as opposed to individualized working relationships. It focuses on the process of becoming established on the London 'scene', presenting qualitative interview data primarily with young workers seeking to build their careers. Musicians may make conscious decisions to pursue types of work which enable greater creative autonomy, but in doing so they may exacerbate fatalism about poor working conditions and undermine professional solidarity. The article also explores how pressures towards 'entrepreneurialism' in other forms of music work constitute further barriers to collective contestation of working conditions. Finally, it points towards types of music work where notions of professional economic interest have more traction.